The Gap in Auditing the Transactions of Islamic Financial Institutions in the Traditional Auditing Environment (International Journal of Financial, Administrative and Economic Sciences, 2024)
Under the name of auditing the transactions of Islamic financial institutions in the environment of traditional auditing, and the spread of work with this name in many countries of the world, this research came to discuss and analyze statistically the ability of Libyan traditional banks to integrate Islamic financial transactions, and the possibility of auditing them according to the provisions and controls of Islamic law.Among the results of the research, which were proven statistically, is the presence of an integration of Islamic financial transactions with traditional financial transactions in Libyan commercial banks by opening windows and windows in them, as well as little understanding and awareness of how to apply the Islamic financial banking system in Islamic banks and windows in Libya, and the lack of correct knowledge by Accountants and auditors for independent audits of traditional banking financial transactions and Islamic financial transactions, in accordance with the provisions and controls of Islamic Sharia for Islamic financial auditing, and in accordance with legislative laws and regulations, Islamic accounting and auditing standards, and financial reporting standards for conventional auditing.
Keywords: Islamic Financial Institutions; Islamic Financial Transactions; The Environment of Traditional Institutions